The Comprehensive Appraisal of COVID-19: Its’ Clinical Panorama from Virology till Management and Beyond - Naqvi, Iftikhar H.; Rizvi, Saiyeda N. Z. (Coronaviruses, 2020)
Severe acute respiratory syndrome, caused by SARS-CoV-2 disease (COVID-19), was first reported in China, and has laid the entire globe at a standstill, with an uncertain future, and a possible economic disaster. The World Health Organization (WHO), on March 11th 2020, avowed COVID-19 a pandemic considering its global pervasiveness. The multi-dimensional challenges include the combat with present available treatment options while simultaneously hastening scientific research for the development of definitive therapeutics and vaccine for this pandemic. The research advancement related to earlier epidemics of severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) by the same coronavirus family provides the understanding of basic and clinical virology, pathogenesis and therapeutics of SARS-CoV-2. The dearth of definitive therapeutics and vaccine renders COVID-19 pandemic a public health challenge globally. This comprehensive review of virology, pathogenesis, and management will abet quarters of public health authorities and medical fraternity to better understand COVID-19.
Keywords: cytokine storm syndrome